Thermodynamic analysis and turbine design of a 100 kW OTEC-ORC with binary non-azeotropic working fluid - Ma, Qingfen; Gao, Zezhou; Huang, Jie; Mahian, Omid; Feng, Xin; Lu, Hui; Wang, Shenghui; Wang, Chengpeng; Tang, Rongnian; Li, Jingru (Energy)
The present paper deals with the performance analysis of an ocean thermal energy conversion (OTEC) plant based on the organic Rankine cycle (ORC) with a theoretical outpower of 100 kW where a non-azeotropic mixture has been used as the working fluid. Hydrofluoroolefins (HFOs) are selected as the components of the binary non-azeotropic working fluid due to their desired thermodynamic properties, higher safety and stability, lower cost and environmental friendliness i.e., zero ODP (Ozone Depletion Potential) and low GWP (Global Warming Potential). In this study, R1224yd(Z) is adopted as the first component due to its lower flammability and toxicity comparing with other HFOs. Through comparisons between several refrigerants, R1243zf was selected as the second component of the binary non-azeotropic working fluid by considering temperature glide and the system efficiency. The performance of OTEC-ORC is also evaluated for two different working fluids i.e., R1224yd(Z)/R1243zf mixture, and pure NH3 (common working fluid in the OTEC-ORC). The optimal composition of the mixed working fluid R1224yd(Z)/R1243zf is obtained of 16:84 with the maximum system efficiency. Next, a gas turbine is designed one-dimensionally and simulated three-dimensionally. The one-dimensional calculation results fit well with the three-dimensional results. At the design point, the turbine output power is 88.63 kW and the efficiency is 87.10%. The thermodynamic findings prove that organic Rankine cycle with binary mixture of R1224yd(Z)/R1243zf is a promising alternative for pure NH3.